Muscle-Specific Sensitivity to Voluntary Physical Activity and Detraining - Hyatt, Jon-Philippe K.; Brown, Emily A.; Deacon, Hannah M.; McCall, Gary E. (Frontiers in Physiology, 2019)
Aerobic physical activity triggers adaptations in skeletal muscle including a fast-to-slow shift in myosin heavy chain (MHC) isoforms, an enhanced capillary network, and mitochondrial biogenesis to meet increased demands placed upon this tissue. Although the magnitude of these responses appears to be dependent on muscle phenotype as well as training volume and/or intensity, the whole-muscle response to detraining remains mostly unexplored. Here, we hypothesized that the shifts toward slower MHC phentotype and the increased capillarity and mitochondrial oxidative markers induced with training would return toward sedentary control levels sooner in the fast plantaris than in the slow soleus muscle as a result of detraining. Soleus and plantaris muscles from eight-week (TR 8wk) voluntarily running adult female Sprague-Dawley rats were compared to muscles from sedentary (SED) and detrained rats (four weeks voluntary running followed by four weeks of reduced activity), which were subdivided into low- (DETR Lo) and high-running-distance (DETR Hi) groups. We show that maintaining the fast-to-slow MHC isoform shift required consistent aerobic training in the soleus and plantaris muscles: detraining clearly abolished any fast-to-slow gains in the plantaris, whereas the training volume in DETR Hi rats appeared to influence the MHC return to basal levels in the soleus. Total capillary number (per mm2) in the plantaris increased in all groups compared to SED levels, but, in the soleus, this enhancement was observed only in the TR 8wk rats. Generally, increased mitochondrial markers for aerobicitiy were observed in TR 8wk plantaris, but not soleus, muscles. In a second experiment, we show that the muscle-specific adaptations were similar after four weeks of voluntary exercise (TR 4wk) as in eight weeks (TR 8wk). Taken together, our findings suggest that the plantaris muscle is more sensitive to voluntary physical activity and detraining than the soleus muscle; these results also demonstrate that the soleus muscle requires a greater aerobic challenge (i.e., intensity, duration) to trigger phenotypic, angiogenic, or aerobic enzyme adaptations. Our findings generally suggest that muscular aerobic fitness to voluntary running, or its loss during detraining, manifests as changes occurring primarily within fast, rather than slow, muscle phenotypes.